Medical Repatriation: Examining the Legal and Ethical Implications of an Emerging Practice - Emily R. Zoellner (Washington University Journal of Law & Policy, 2010)
Because medical repatriation implicates both legal and ethical questions, any proposal attempting to mitigate its problems must be similarly multifaceted and address both the legal and ethical issues involved. This Note puts forth two proposals. The first involves changing the Code of Federal Regulations to create legal standards limiting the practice of medical repatriation. Additionally, it would more broadly and clearly define the circumstances in which hospitals can receive funding for treatment of undocumented immigrants. The second proposal clarifies the American Medical Association‘s Principles of Medical Ethics with respect to the effect of patients‘ immigration status on the applicability of medical ethics standards. This Note asserts that changes are necessary to both legal regulations on medical repatriation and medical ethics standards. Part I of the History section explains the relevance of medical repatriation and anticipates its likely future, absent new regulations. Part II.A of the History section discusses the evolution of medical repatriation, focusing on the lack of government funding available for treatment of undocumented immigrants and the concurrent mandate that hospitals treat all patients with emergent medical conditions. Part II.B reviews medical ethical standards and examines the interplay between ethical and legal standards. Next, this Note analyzes the various factors contributing to the emergence of medical repatriation and evaluates whether the practice comports with currently established legal and ethical standards. Finally, this Note proposes (1) changes to the federal regulations governing hospitals and (2) clarifications to the ethical standards with which the medical profession strives to comply.
Keywords: Repatriation; Emigration & amp; immigration; Health care industry – Law & amp; legislation; United States. Personal Responsibility & amp; Work Opportunity Reconciliation Act of 1996; Deportation; Illegal immigrants; Medical ethics; Medically uninsured persons; Patient dumping